Future land use threats to range‐restricted fish species in the United States. Issue 6 (4th March 2016) - Januchowski‐Hartley, Stephanie R.; Holtz, Lauren A.; Martinuzzi, Sebastian; McIntyre, Peter B.; Radeloff, Volker C.; Pracheil, Brenda M.
Abstract: Aim: Land use change is one major threat to freshwater biodiversity, and land use change scenarios can help to assess threats from future land use change, thereby guiding proactive conservation decisions. Our goal was to identify which range‐restricted freshwater fish species are most likely to be affected by land use change and to determine where threats to these species from future land use change in the conterminous United States are most pronounced. Location: United States of America. Methods: We focused on range‐restricted freshwater fish species, identified which of these species are considered threatened based on either the International Union for the Conservation of Nature (IUCN)'s Red List or the Endangered Species Act (ESA), and compared their distributions to patterns of future land use changes by 2051 under three scenarios. Results: We found that 14% of the range‐restricted species had >30% of their distribution area occupied by intensive land use in 2001, and this number increased from 27 to 58% by 2051 depending on the land use scenario. Among the 57 species most likely to be strongly affected by intensive land use, only 26% of these species are currently listed as threatened on the IUCN Red List, and 12% are listed as threatened under the ESA. Main conclusions: Our approach demonstrates the value of considering future land use change scenarios in extinction risk assessment frameworks and offers guidelines for how this could be achieved for future assessments.